2017
DOI: 10.5194/esurf-5-669-2017
|View full text |Cite
|
Sign up to set email alerts
|

Bedload transport measurements with impact plate geophones in two Austrian mountain streams (Fischbach and Ruetz): system calibration, grain size estimation, and environmental signal pick-up

Abstract: Abstract. The Swiss plate geophone system is a bedload surrogate measuring technique that has been installed in more than 20 streams, primarily in the European Alps. Here we report about calibration measurements performed in two mountain streams in Austria. The Fischbach and Ruetz gravel-bed streams are characterized by important runoff and bedload transport during the snowmelt season. A total of 31 (Fischbach) and 21 (Ruetz) direct bedload samples were obtained during a 6-year period. Using the number of geop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 40 publications
(58 reference statements)
5
35
0
Order By: Relevance
“…An array of steel plates is typically installed flush with the surface of a sill or check dam, a location where there is only a small chance for (substantial) deposition of bed load grains during transport conditions. The Fischbach and Ruetz field sites are operated by the Tyrolean Water Power Company (TIWAG; Rickenmann & Fritschi, ; Turowski et al, ). They are located in partly glaciated catchments in the Tyrolean Alps (supporting information Figure S1).…”
Section: Field Sites Geophone Measurements and Data Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…An array of steel plates is typically installed flush with the surface of a sill or check dam, a location where there is only a small chance for (substantial) deposition of bed load grains during transport conditions. The Fischbach and Ruetz field sites are operated by the Tyrolean Water Power Company (TIWAG; Rickenmann & Fritschi, ; Turowski et al, ). They are located in partly glaciated catchments in the Tyrolean Alps (supporting information Figure S1).…”
Section: Field Sites Geophone Measurements and Data Analysismentioning
confidence: 99%
“…A detailed analysis showed that there is pickup of geophone signal very probably due to vehicle traffic on the road (Fischbach) and paved parking lot (Ruetz) which are located very close to the measuring sill, resulting in implausible geophone impulse counts that could be clearly identified at smaller discharges. This analysis concluded that bed load transport is likely the dominant source of producing geophone impulses above a critical discharge Q c of about 3.5 m 3 s −1 at the Fischbach, and above a Q c of about 1.5 m 3 s −1 at the Ruetz (Rickenmann & Fritschi, ). A quantitative analysis comparing the mean impulses for all eight geophone sensors for periods in winter (16 October to 14 April) and in summer for flows with Q < Q c suggests that a large part of the geophone signal in summer during these flow conditions may be due to vehicle traffic (supporting information Table S1); however, traffic may considerably vary seasonally, particularly with the important winter tourism activity in the Ruetz catchment, complicating a detailed quantification of this effect.…”
Section: Field Sites Geophone Measurements and Data Analysismentioning
confidence: 99%
See 3 more Smart Citations